2017
DOI: 10.21767/2574-2825.100022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planned Health Educational Program on Menstrual Knowledge and Practices among Adolescent Saudi Girls

Abstract: Objectives: To assess knowledge, practices and quality of life of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care. To find the relation between knowledge, practices and selected variables of quality of life of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care. To evaluate the outcome and impact of health education program on knowledge and practices of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care.Methods: An experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…Their understanding has been signicanty improved in the postintervention process. Such results were consistent with other studies conducted in Egypt, Saudi Arabia and India [10][11][12]. In our study, knowledge on cause of menstruation was poor among participants i.e.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Their understanding has been signicanty improved in the postintervention process. Such results were consistent with other studies conducted in Egypt, Saudi Arabia and India [10][11][12]. In our study, knowledge on cause of menstruation was poor among participants i.e.…”
Section: Methodssupporting
confidence: 93%
“…Menstruation is an important aspect in a girl's reproductive health. Thus, health education in menstrual hygiene is very necessary for adolescence girl to cope with menstruation and maintain good menstrual hygiene [10]. The current study found that the average awareness score of adolescent girls was poor before the menstrual health education program was introduced; whilst it played a crucial role in increasing their level of knowledge after it has been implemented.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, the score of QoL of adolescents in the intervention group was significantly higher than the control group at T2. These results were in line with a previous study in Saudi adolescent girls (Aburshaid et al, 2017). In our study, one could interpret that the participants required information about puberty and when the need for their awareness was met, their QoL also increased.…”
Section: Discussionsupporting
confidence: 94%
“…were in line with a previous study in Saudi adolescent girls (Aburshaid et al, 2017). In our study, one could interpret that the participants required information about puberty and when the need for their awareness was met, their QoL also increased.…”
Section: Discussionsupporting
confidence: 92%